Strategies of Defending Theism against the Accusation of the Hiddenness: A Reply to Discussants - Dobrzeniecki, Marek (Roczniki Filozoficzne, 2023)
The article is a response to the critical comments by Stanisław Judycki, Ryszard Mordarski, Marek Pepliński and Jan Sochoń on the book Ukrytość i Wcielenie. Teistyczna odpowiedź na argument Johna L. Schellenberga za nieistnieniem Boga [Hiddenness and the Incarnation: A Theistic Response to John L. Schellenberg’s Argument for Divine Nonexistence]. The main objection to my position is that it is too favorable to J. L. Schellenberg’s argument, which should not necessarily be a model for addressing the issue of the divine hiddenness. One of the expressions of accepting the assumptions of the Canadian author is my acceptance of the proposition affirming the existence of non-resistant nonbelievers.